2017
DOI: 10.1159/000479824
|View full text |Cite
|
Sign up to set email alerts
|

Presence of Initial Caries Lesions as a Risk Factor for Caries in Preschool Children: A Cohort Study

Abstract: The aim of this study was to evaluate the influence of initial noncavitated caries lesions on cavitated caries increment in preschool children. A 2-year cohort study was designed to include the participants of a survey on dental caries performed in 2010. Preschool children (12-59 months old) were examined for dental caries and classified as children with no caries lesions, with only initial lesions, with at least 1 moderate caries lesion, and with extensive lesions. Socioeconomic data were also collected. Afte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 21 publications
(47 reference statements)
4
13
0
Order By: Relevance
“…Ours results are consistent with recent studies, which highlighted through longitudinal designs, the caries experience influencing the developing of future child injuries 4,20 . In our study, the standardized coefficient for the path between dental caries experience at baseline and the increment of caries lesions was highly significant ( P < .01), which supports the direct influence of this factor on subsequent records of the disease.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Ours results are consistent with recent studies, which highlighted through longitudinal designs, the caries experience influencing the developing of future child injuries 4,20 . In our study, the standardized coefficient for the path between dental caries experience at baseline and the increment of caries lesions was highly significant ( P < .01), which supports the direct influence of this factor on subsequent records of the disease.…”
Section: Discussionsupporting
confidence: 93%
“…Household income was collected in Reais (Brazilian currency ‐ R$4.00 was equivalent to US$1.00 approximately) considering the sum of all family income and was used as a continuous variable 9 . Household crowding was evaluated through the ratio of the number of individuals by the number of rooms in the house and used as a continuous variable 20 …”
Section: Methodsmentioning
confidence: 99%
“…Caries lesions have a dynamic evolution requiring a long time, usually many months or years. In younger children, initial caries lesions have been considered as a predictor of caries progression [27].…”
Section: Discussionmentioning
confidence: 99%
“…However, it is not an ideal approach, as it is not conducive to the early prevention of dental caries. A 2-years cohort study reported not only that moderate and severe caries were associated with caries incidence but also that the initial caries were associated with caries incidence (40). To determine the initial factors for caries onset, only individuals whose D1-6MFT score was "0" were included in the further analysis.…”
Section: Discussionmentioning
confidence: 99%